STRATEGI DINAS TENAGA KERJA DALAM MENEKAN ANGKA KECELAKAN KERJA DI KOTA PEKANBARU (Studi Kasus PT. Riau Crumb Rubber Factory Pekanbaru) - Angga Sony A.M.; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Work accident is one of the main problems in the Employment sector. To overcome problem work accident is needed a policy that accommodate the rights of workers in doing the work called protection labor. Strategy of the Department of Labor is the measures that have been planned and implemented by the Department of Labor in the performance of labor protective measures according to the vision and mission of the organization.This research aims to find out how strategies of the Department of Labor and factors affecting the strategy set forth by the Department of labor of Pekanbaru.This research used a qualitative approach by using a method of snowball sampling with data collecting technique by means of an interview, observation and documentation.Results of the research is a strategy Department of Labor in Pressing Numbers Work Accident in Pekanbaru city was not effective since the Department of Labor hasn't been able to optimize the power and opportunities owned by the Department of labor. Factors that affect the strategy of the Department of labor in Pressing work accident Rate among other things: the quality and quantity of human resources, maximizing socialization and need to surveillance periodically.Keywords: Work Accident, Strategy, Labor Protection.